The Role of Ampo As an Adsorbent for Reducing Peroxide Value in Used Cooking Oil - Susilowati; Khanza Lolita Astya; Ulinnuha Syaiful Bachri (Nusantara Science and Technology Proceedings, 2020)
In daily life, cooking oil has a very important role. Cooking oil itself has a usage limit. If the cooking oil has a rancid smell and turns brown, the cooking oil is not suitable for reuse. Naturally, cooking oil can only be used 2-3 times. To extend the life of cooking oil and improve its quality so that it can be reused, an adsorption process is carried out to adsorb harmful substances in used cooking oil. In this research, Ampo adsorbent is used which has the advantage of being environmentally friendly and edible. The procedures carried out in this study include the initial analysis of used cooking oil, activation of the Ampo as an adsorbent, the adsorption process by varying the mass of Ampo 70, 75, 80, 85, 90 grams and stirring time of 30, 60, 90, 120, 150 minutes and analysis of peroxide value on the adsorbed used cooking oil. The optimal condition of the research is that for the adsorption process using Ampo as adsorbent on used cooking oil, namely by stirring for 60 minutes and Ampo mass of 75 grams. This condition can reduce the peroxide value by up to 93%. While the maximum adsorption power of the Ampo adsorbent was obtained from the proving of the Freundlich isotherm equation theory with a value of 14,6487 mg/gram.